2008
DOI: 10.1136/jmg.2008.061234
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the HPGD gene encoding NAD+ dependent 15-hydroxyprostaglandin dehydrogenase underlies isolated congenital nail clubbing (ICNC)

Abstract: The involvement of 15-PGDH in the pathogenesis of ICNC may open up interesting perspectives into the function of this enzyme in nail morphogenesis/development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 31 publications
3
35
1
3
Order By: Relevance
“…6,7 Recently, a homozygous missense mutation in HPGD has been identified in a single family affected with isolated congenital nail clubbing as an autosomal-recessive trait. 9 In this study, we found significant linkage of COA to a region harboring the HPGD gene in one affected family and report novel mutations in HPGD causing COA in two families. However, in a third family with dominant inheritance of isolated digital nail clubbing, we found no mutation in HPGD indicating another underlying gene defect.…”
Section: Two Variants Of Pho Have Been Distinguished Clinically (Suppmentioning
confidence: 58%
See 3 more Smart Citations
“…6,7 Recently, a homozygous missense mutation in HPGD has been identified in a single family affected with isolated congenital nail clubbing as an autosomal-recessive trait. 9 In this study, we found significant linkage of COA to a region harboring the HPGD gene in one affected family and report novel mutations in HPGD causing COA in two families. However, in a third family with dominant inheritance of isolated digital nail clubbing, we found no mutation in HPGD indicating another underlying gene defect.…”
Section: Two Variants Of Pho Have Been Distinguished Clinically (Suppmentioning
confidence: 58%
“…7,9,14 Two of four mutations detected so far result in truncation of the HPGD transcript due to nucleotide deletions. 7,9,14 These two mutations alter the open reading frame and result in truncated proteins, which lack the PGD 2 -binding domain. 7 By analyzing the crystal structure of HPGD, the reported homozygous amino-acid substitution Ala140Pro is predicted to disrupt binding of PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• периостоз обусловлен PgE2-опосредованной стимуля-цией активности остеобластов и остеокластов за счет повышения VEGF [20]; • пахидермия возникает вследствие чрезмерного синте-за внекостного матрикса фибробластами, обусловлен-ного гиперсекрецией VEGF и фактора роста тромбоци-тов (PDGF) [21]; • утолщение концевых фаланг пальцев происходит за счет увеличения пролиферации фибробластов и пе-риферической вазодилатационной активности PgE2 посредством повышения концентрации PDGF [22]; • задержка постнатального закрытия артериального (Бо-таллова) протока (в 25% случаев при наличии мутации в гене HPGD против 0,5% встречаемости в общей попу-ляции [11,23]) связана с отсутствием быстрого падения циркуляции простагландина Е2 после установления ле-гочного дыхания [11]; • гиперпигментация и утолщение волос и ресниц объяс-няется наличием рецепторов к PgE2 в волосяных фол-ликулах [24];…”
Section: Discussionunclassified